Vibration suppression for monopile and spar‐buoy offshore wind turbines using the structure‐immittance approach. Issue 10 (7th July 2020) - Li, Yi‐Yuan; Park, Semyung; Jiang, Jason Zheng; Lackner, Matthew; Neild, Simon; Ward, Ian
Abstract: Offshore wind turbines have the potential to capture the high‐quality wind resource. However, the significant wind and wave excitations may result in excessive vibrations and decreased reliability. To reduce vibrations, passive structural control devices, such as the tuned mass damper (TMD), have been used. To further enhance the vibration suppression capability, inerter‐based absorbers (IBAs) have been studied using the structure‐based approach, that is, proposing specific stiffness‐damping‐inertance elements layouts for investigation. Such an approach has a critical limitation of being only able to cover specific IBA layouts, leaving numerous beneficial configurations not identified. This paper adopts the newly introduced structure‐immittance approach, which is able to cover all network layout possibilities with a predetermined number of elements. Linear monopile and spar‐buoy turbine models are first established for optimisation. Results show that the performance improvements can be up to 6.5% and 7.3% with four and six elements, respectively, compared with the TMD. Moreover, a complete set of beneficial IBA layouts with explicit element types and numbers have been obtained, which is essential for next‐step real‐life applications. In order to verify the effectiveness of the identified absorbers with OpenFAST, an approach has been established to integrate any IBA transfer functions. It has been shown that the performance benefits preserve under both the fatigue limit state (FLS) and the ultimate limit state (ULS). Furthermore, results show that the mass component of the optimum IBAs can be reduced by up to 25.1% (7, 486 kg) to achieve the same performance as the TMD.